2015
DOI: 10.1123/ijspp.2014-0233
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Accelerometer and Time–Motion Data in Elite Men’s Hockey Training and Competition

Abstract: The strong relationship between these variables suggests that PL in hockey is mostly accumulated through running and other locomotor actions, such that PL is not effective in quantifying other activities (evasion, low stance) that contribute to physiological demands, particularly in training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
5
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 11 publications
3
40
5
1
Order By: Relevance
“…PlayerLoad TM has previously been shown to be highly positively correlated with the volume of locomotion performed in team sports (Polglaze, Dawson, Hiscock, & Peeling 2015;Scott, Lockie, Knight, Clark, & Janse De Jonge 2013). As such, examination of the absolute PL response would inherently reflect the typical in match total distance response typically shown to reduce within and across halves (Barrett et al, 2016a;Mohr et al 2003;Rampinini et al, 2009;Weston et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…PlayerLoad TM has previously been shown to be highly positively correlated with the volume of locomotion performed in team sports (Polglaze, Dawson, Hiscock, & Peeling 2015;Scott, Lockie, Knight, Clark, & Janse De Jonge 2013). As such, examination of the absolute PL response would inherently reflect the typical in match total distance response typically shown to reduce within and across halves (Barrett et al, 2016a;Mohr et al 2003;Rampinini et al, 2009;Weston et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Instead, measuring the accelerations based on Newton's second law (with a certain mass, accelerations are proportional to the external forces acting on the body) is more feasible. The availability of low-cost inertial sensors has led to the integration of accelerometers in commercially available GPS units, and this in turn has led to an expansion of the literature towards evaluating reliability of accelerometry-based variables (20)(21)(22)(23) and their utility to assess training load in various situations (24)(25)(26)(27) and sporting populations (23,24,(28)(29)(30).…”
Section: Monitoring External Loadmentioning
confidence: 99%
“…Scientists have attempted to relate this to the physiological load (external or internal measures), similar to what is commonly done in physical activity monitoring (as reviewed in (40,41)). For example, one study demonstrated moderate to high relationships between PlayerLoad TM and distance covered (29,42), while other studies have demonstrated a moderate to high relationship between PlayerLoad TM and ratings of perceived exertion (RPE) (42)(43)(44) and trivial to moderate relationship between PlayerLoad TM and ̇2 or heart rate data, respectively (20,42,45). These relationships between measures of physiological and biomechanical loads lack a solid foundation, except for the fact that in running-based team sports the variations in both types of loads are generally experienced together.…”
Section: Monitoring External Loadmentioning
confidence: 99%
“…Por otro lado, a nivel colectivo, una mayor alternancia en la posesión del balón en jugadores sub13 menos expertos (Folgado, Lemmink, Frencken, & Sampaio, 2014) podría ser la causa de que los jugadores se vieran obligados a alternar continuamente las labores ofensivas y defensivas, provocando un mayor número de cambios de dirección, una mayor carrera no lineal o un juego más desordenado (Sampaio & Maçãs, 2012), lo que podría favorecer un aumento de aceleraciones, desaceleraciones y cambio de dirección. Recientemente se ha comenzado a proponer ratios entre la distancia total de carrera y el PL como métrica para valorar la eficiencia de la carrera o tipología de la tarea (Polglaze, Dawson, Hiscock, & Peeling, 2015), por poner algunos ejemplos. Sería conveniente realizar más investigación al respecto para conocer los motivos de por qué supone la misma tarea una mayor carga respecto al indicador global de aceleración, sabiendo que el Player Load es un indicador 'personal'.…”
Section: Discussionunclassified